Influence of surface properties on the performance of Cu(In, Ga)(Se, S)2 thin-film solar cells using Kelvin probe force microscopy. Issue 51 (5th May 2015) - Yang, JungYup; Lee, Dongho; Huh, KwangSoo; Jung, SeungJae; Lee, JiWon; Lee, HeeChan; Baek, DoHyun; Kim, ByoungJune; Kim, Dongseop; Nam, Junggyu; Kim, GeeYeong; Jo, William
Abstract : We have investigated the sulfurization process in a Cu(In, Ga)(Se, S)2 absorber layer fabricated by a two-step sputter and selenization/sulfurization method in order to make an ideal double-graded band-gap profile and increase the open circuit voltage. Abstract : We have investigated the sulfurization process in a Cu(In, Ga)(Se, S)2 (CIGSS) absorber layer fabricated by a two-step sputter and selenization/sulfurization method in order to make an ideal double-graded band-gap profile and increase the open circuit voltage ( V oc ). The sulfurization process was controlled by temperature from 570 °C to 590 °C without changing H2 S gas concentration and reaction time. Although the energy band-gap of the CIGSS absorber layer was increased with increasing sulfurization temperature, the V oc of the completed CIGSS device fabricated at 590 °C sulfurization temperature did not increase. In order to investigate this abnormal V oc behavior, the CIGSS absorber layer was measured by local electrical characterization utilizing Kelvin probe force microscopy, especially in terms of grain boundary potential and surface work function. Consequently, the abnormal V oc behavior was attributed to the degradation of grain boundary passivation by the strong sulfurization process. The optimum sulfurization temperature plays an important role in enhancement of grain boundary passivation. It was also verified that the V oc degradation in the CIGSS solar cell fabricated by the two-step method is more influenced by the grain boundary passivation quality in comparison with the slight non-uniformity of material composition among grains.